Studi Analitik Penambahan Reflektor Pelat Datar Sudut 60˚ pada Pemanas Air Tenaga Surya - Ashari, Dedy; Ichsani, Djatmiko (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2023)
The condition of electrical energy in Indonesia is increasing every year, one of which is used as a water heater. Various methods have been used to increase the efficiency of solar water heaters, including the use of flat plate reflectors. This research was carried out analytically to determine daily solar radiation intensity data on solar collectors with the addition of a 60˚ angle reflector. The results obtained in conditions without reflectors, the daily average solar radiation value produced by solar collectors is 1136 W/m2. Then for the condition of the reflector angle of 60˚, the daily average solar radiation value is recorded at 1386 W/m2. There is a difference of 250 W/m2 between the two conditions. The daily solar radiation intensity value is also calculated using the area method, the result is a daily solar radiation value of 2.542 kWh/m2 in conditions without the reflectors. Furthermore, at a reflector angle of 60˚, the resulting solar radiation value increases by 6% to 2.712 kWh/m2. The addition of a flat plate reflector at an angle of 60˚ is proven to increase the daily solar radiation intensity value that can be received by a solar water heater.